Hands-on RESTful API design patterns and best practices design, develop, and deploy highly adaptable, scalable, and secure RESTful web APIs - Subramanian, Harihara; Chelliah, Pethuru Raj ca. 20./21. Jahrhundert (Packt, 2019)
bBuild effective RESTful APIs for enterprise with design patterns and REST framework's out-of-the-box capabilities/b h4Key Features/h4 ulliUnderstand advanced topics such as API gateways, API securities, and cloud /li liImplement patterns programmatically with easy-to-follow examples /li liModernize legacy codebase using API connectors, layers, and microservices /li /ul h4Book Description/h4 This book deals with the Representational State Transfer (REST) paradigm, which is an architectural style that allows networked devices to communicate with each other over the internet. With the help of this book, you'll explore the concepts of service-oriented architecture (SOA), event-driven architecture (EDA), and resource-oriented architecture (ROA). This book covers why there is an insistence for high-quality APIs toward enterprise integration.